Asuhan Keperawatan Sistem Saraf pada Ny.Y dengan Diagnosa Medis Post Craniotomy: ICH+Pneumonia di ICU Rumah Sakit Royal Prima Medan - Yantriani Talunohi; Sami E. Tamba; Sofia A. Simanullang; Lidya Afriani Br Berutu; Giofanny Zega; Afeus Halawa (Journal of Health, Medical, and Psychological Studies, 2026)
This study aims to describe the implementation of neurological nursing care for patient Mrs. Y, who was diagnosed with post-craniotomy: intracerebral hemorrhage (ICH) complicated by pneumonia, in the ICU at Royal Prima Hospital in Medan in 2026. The research method used an empirical approach with a descriptive case study design through clinical observation, physical examination, family interviews, and documentation of the patient’s medical records during the intensive care period. The assessment results indicated that the patient experienced decreased consciousness, impaired oxygenation, increased secretion production, hyperthermia, and hemodynamic instability, leading to the nursing diagnoses of ineffective airway clearance, ineffective cerebral tissue perfusion, and hyperthermia. Nursing interventions were implemented through neurological monitoring, head-up positioning, suctioning, oxygen therapy, infection prevention, and gradual passive mobilization. Evaluation showed an increase in the Glasgow Coma Scale score, improved oxygen saturation, a decrease in body temperature, and reduced respiratory secretion production. Systematic and collaborative nursing care contributed to the stabilization of the patient’s neurological and respiratory conditions during ICU care.